2012
DOI: 10.1111/j.1365-3040.2012.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon trading for phosphorus gain: the balance between rhizosphere carboxylates and arbuscular mycorrhizal symbiosis in plant phosphorus acquisition

Abstract: Two key plant adaptations for phosphorus (P) acquisition are carboxylate exudation into the rhizosphere and mycorrhizal symbioses. These target different soil P resources, presumably with different plant carbon costs. We examined the effect of inoculation with arbuscular mycorrhizal fungi (AMF) on amount of rhizosphere carboxylates and plant P uptake for 10 species of low-P adapted Kennedia grown for 23 weeks in low-P sand. Inoculation decreased carboxylates in some species (up to 50%), decreased plant dry wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
136
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 53 publications
8
136
3
1
Order By: Relevance
“…When a large fraction of total soil P is sorbed, carboxylate-releasing strategies are desirable. Some species use this strategy when non-mycorrhizal, suppressing it when inoculated by mycorrhizas [67], showing there is no sharp boundary between mycorrhizal and carboxylatereleasing species. Cluster roots are likely the very best strategy when P is very poorly available.…”
mentioning
confidence: 99%
“…When a large fraction of total soil P is sorbed, carboxylate-releasing strategies are desirable. Some species use this strategy when non-mycorrhizal, suppressing it when inoculated by mycorrhizas [67], showing there is no sharp boundary between mycorrhizal and carboxylatereleasing species. Cluster roots are likely the very best strategy when P is very poorly available.…”
mentioning
confidence: 99%
“…In rice it was shown that the ability of varieties to acquire Zn through the mycorrhizal pathway was negatively correlated with (and hence traded off against) the ability to acquire Zn in the non-mycorrhizal condition (Gao et al 2007). The same negative correlation and trade-off was found for members of the genus Kennedia (Ryan et al 2012). It has been demonstrated that there are architectural tradeoffs between adventitious and basal roots (Walk et al 2006;Zhu and Lynch 2004).…”
Section: Amf Functioning In Plant-plant Interactionssupporting
confidence: 64%
“…Such a trade-off has been reported for rice, where increased Zn uptake through organic anions and through the mycorrhizal symbiosis could not be stacked (Gao et al 2012). Downregulation of organic anion production in the genus Kennedia in the mycorrhizal condition also suggests a trade-off (Ryan et al 2012). However, Lynch (2007) suggested that root hairs and the symbiosis with AMF could be combined and do not show a trade-off.…”
mentioning
confidence: 78%
“…Carboxylates may act as bio-stimulating agents in the degradation of PHCs through the provision of a labile carbon source that supports increased microbial growth and activity. When added to soils, carboxylates are rapidly degraded by soil microorganisms, with up to 80 % mineralized to CO 2 within 24 h, depending upon the carboxylate added and the soil type (Evans, 1998;Ström et al, 2001;Hashimoto, 2007;Oburger et al, 2009;Fujii et al, 2010;Ryan et al, 2012). In addition, carboxylates have the capacity to enhance soil phosphorus supply and, hence, microbial growth and activity through phosphate desorption either due to anion exchange or their ability to chelate to metal cations (e.g., Al 3+ , Fe 3+ and Ca 2+ ) (Jones and Darrah, 1994;Ryan et al, 2001;Shane and Lambers, 2005).…”
Section: Introductionmentioning
confidence: 99%